Methylglyoxal Acts as a Tumor-Promoting Factor in Anaplastic Thyroid Cancer - Cinzia Antognelli (Cells, 2019)
Methylglyoxal (MG) is a potent inducer of advanced glycation end products (AGEs). MG, long considered a highly cytotoxic molecule with potential anticancer value, is now being re-evaluated to a protumorigenic agent in some malignancies. Anaplastic thyroid cancer (ATC) is an extremely aggressive and highly lethal cancer for which conventional therapies have proved ineffective. Successful therapeutic intervention in ATC is undermined by our poor understanding of its molecular etiology. In the attempt to understand the role of MG in ATC aggressiveness, we used immunohistochemistry to examine the level of MG protein adducts in ATC and slow-growing papillary thyroid cancer (PTC). We detected a high level of MG adducts in ATC compared to PTC ones, suggesting a protumor role for MG-mediated dicarbonyl stress in ATC. Accordingly, MG adduct accumulation in ATC cells in vitro was associated with a marked mesenchymal phenotype and increased migration/invasion, which were both reversed by aminoguanidine (AG)—a scavenger of MG—and resveratrol—an activator of Glyoxalase 1 (Glo1), the key metabolizing enzyme of MG. Our study represents the first demonstration that MG, via AGEs, acts as a tumor-promoting factor in ATC and suggests that MG scavengers and/or Glo1 activators merit investigations as potential therapeutic strategies for this malignancy.